Grammar and Translation: The Noun + Noun Conundrum - Bagge, Christine; Manning, Alan (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis article deals with the vexed question regarding the translation into French of English NOUN1 + NOUN2 sequences. Using the 15 meaning categories presented by Biber et al. (1999: 589-591), with some modifications and corrections, the authors expand each category into 20 representative items and translate them into French; they then show, by means of case study based on the translation into French of several noun sequences, that students whose first language is English seem to have difficulty rendering certain of these structures; by contrast, students participating in the study whose first language is French tend to commit errors not made by their English counterparts. The pedagogical implications of this pilot project are pointed up, and new linguistic developments concerning the use NOUN1 + NOUN2 in French are identified.